Combining Ability for Growth, Yield and Related Traits In Cucumber (Cucumis Sativus L.) Under Subtropical Conditions of Garhwal Himalayas (Bangladesh Journal of Botany, 2021)
To assess the combining ability for quantitative and qualitative traits in cucumber a full diallel set of 7 parents and their 42 F1’s was evaluated at Horticultural Research Centre, Department of Horticulture, H.N.B. Garhwal University, Srinagar (Garhwal), Uttarakhand, India during 2015 and 2016. The mean sum of squares due to general combining ability (GCA) was of significant differences at 1 % level for almost all the characters. The variance due to specific combining ability (SCA) was found highly significant at 1 % level for almost all the characters. Results from general combining ability studies revealed that the parent, New Manipur-1 showed significant GCA effect in desired direction for maximum characters viz., length of vine, days to first fruit harvest and number of fruits per vine. The cross combinations, Seven Star x New Manipur-1 for length of vine, Swarna Purna x Seven Star for days to first fruit harvest; K-90 x Seven Star for number of fruits per vine and the cross PB-Naveen x Swarna Purna for total fruit yield per vine showed significant SCA effect in desired direction and found to be superior specific cross combinations.Bangladesh J. Bot. 50(4): 1003-1010, 2021 (December)